The Effectiveness of In-distance Alternative Evaluation according to the Point of View of the Female Students of the College of Education at Umm for the year 1443 AH - Al-Qahtani, Tahani Fehan (Journal of Educational and Psychological Sciences, 2022)
The current study aimed at the effectiveness of distance alternative evaluation from the point of view of the female students of the College of Education at Umm Al-Qura University. The research used the descriptive approach to achieve the objectives of the research, (45) items were formulated distributed on three branches, and the scale was applied on a sample of (638) female students from the College of Education from Umm Al-Qura University. By computing the means and independent samples t-test, the following results were reached: The level of distance alternative evaluation among female students of the College of Education at Umm Al-Qura University was in a high degree with a mean (3.81), and the results also showed that there were statistically significant differences at the (0.05) level on the degrees of distance alternative evaluation scale among female students of the College of Education at Umm Al-Qura University attributed to the study stage (bachelor's degree - postgraduate studies) in favor of the undergraduate students. Some recommendations were made, such as holding theoretical and practical courses on female students containing the importance, advantages, practices and applications of distance alternative evaluation.
Keywords: Evaluation effectiveness; Distance alternative evaluation; College of Education female students